Different levels of inclusion of flour made from cooked Nile tilapia carcasses in homemade bread (Research, Society and Development, 2021)
The objective of this work was to develop and evaluate the nutritional and microbiological quality and acceptance of homemade bread including fish meal. Breads with inclusion of 0, 5, 10 and 15% of flour made from cooked carcasses of Nile tilapia were developed, with proximate, microbiological and sensory composition analysis being carried out. Breads with 10% inclusion of fish flour had lower moisture content, and as the inclusion of fish meal in bread increased linearly the ash content. It was not possible to observe significant difference between treatments for crude protein content. Regarding the sensory analysis, the tasters observed a significant difference with the inclusion of fish meal in homemade breads, where there was a negative linear effect for all sensory parameters evaluated. The replacement of wheat flour in concentrations above 5% resulted in loaves with lower acceptance scores for the attributes color, flavor, appearance and overall appearance. The results obtained in the microbiological analysis of breads including flour from cooked fish carcasses indicated a low number of coliforms at 35 °C and 45 °C, coagulase positive Staphylococci and absence of Salmonella spp, showing that the breads were able to human food, being within the microbiological standards required by law. Thus, the inclusion of cooked carcass flour in homemade bread is an excellent alternative for adding value to the fishing industry's waste.